Stylistics Literature in Qashidah Burdah by Imam Abu Abdillah bin Sa’id Al-Bushiry - Asep Sopian; Mad Ali; Nur Latifah (Universitas Pendidikan Indonesia, 2022)
Qashidah burdah is rich in linguistic style and content, however it is regrettable that many readers simply read without experiencing the beauty of language and the depth of meaning. Stylistic analysis may be used to examine the usage of linguistic style in literature and its consequences for meaning. The goal of this research is to define the components that influence the stylistics and linguistic style of qashidah burdah. To accomplish this purpose, a form of qualitative study using a content analysis technique was applied. According to the findings of the phonological analysis of qashidah burdah chapters 9 and 10, sawamit (consonant), sawait (vowel), and qafiyah (verse) were evaluated from a phonological aspect; As for the lexical aspect, there are 7 pairs of words at-Taraduf (synonyms) and a pair of adh-Dhiddhu (antonyms); From the grammatical aspect there is taqdim ta'khir and from the morphological aspect there is Ikhtiyar al-Sighah, al-'Uduul bi al-Sighah 'an al-Asl al-Siyaqi, Al-idmar fi maudi', and al-Izdiwaajiyah; from the aspect of language style there are assonance, alliteration, anastrophe, apostrophe, polysyndeton, ellipsis, and euphemism; and aspect of rhetoric there is simile, metaphor, epithet, synecdoche, irony, and personification..